Identifikasi kesulitan dan kebutuhan belajar peserta Uji Kemahiran Berbahasa Indonesia (UKBI) di Provinsi Jambi - Ernanda, Ernanda; Pratama, Deri Rachmad; D, Yusra; Rasdawita, Rasdawita (Proceedings Academic Universitas Jambi, 2025)
This study aims to identify the difficulties and learning needs of participants of the Indonesian Language Proficiency Test (UKBI) from various backgrounds, including students and professionals. UKBI serves as a standard for assessing Indonesian language proficiency in academic and professional contexts. This study employs a quantitative approach involving 68 respondents who have previously taken the UKBI at the Jambi Province Language Center. The instrument used was a questionnaire covering respondents’ personal data, general and specific difficulties for each UKBI skill, as well as participants’ learning needs, with responses provided using a 5-point Likert scale. The data were analyzed through data reduction, categorization, and thematic analysis to gain a comprehensive understanding of the participants’ challenges and learning needs. The results of the study show that grammar was the most challenging component of the Indonesian Language Proficiency Test (UKBI). Respondents did not consider reading and listening to be the most difficult sections of the test. Additionally, the respondents indicated a need for more guidance in grammar, which had the highest percentage of difficulty at 85.3%.